Stable and convergent finite difference schemes on nonuniformtime meshes for distributed-order diffusion equations - Morgado, M. Luísa (2021)
In this work, stable and convergent numerical schemes on nonuniform time meshes are proposed, for the solution of distributed-order diffusion equations. The stability and convergence of the numerical methods are proven, and a set of numerical results illustrate that the use of particular nonuniform time meshes provides more accurate results than the use of a uniform mesh, in the case of nonsmooth solutions.